2004
DOI: 10.1002/gps.1078
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cholesterol levels and depression in the elderly

Abstract: In the present cross sectional study, there was no association between depression and low serum cholesterol levels after adjusted for confounding factors. Further studies are needed to clarify this suggestion with larger number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 33 publications
0
17
0
3
Order By: Relevance
“…Numerous cohort studies (on non-depressed subjects) have assessed the relationship between plasma cholesterol and mood disorders with contradictory results [49,[61][62][63][64]. Several possible explanations exist for these mixed findings.…”
Section: Affective Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous cohort studies (on non-depressed subjects) have assessed the relationship between plasma cholesterol and mood disorders with contradictory results [49,[61][62][63][64]. Several possible explanations exist for these mixed findings.…”
Section: Affective Disordersmentioning
confidence: 99%
“…The fact that plasma fatty acids reflect dietary intake of the last few days could influence the results of those studies. Second, people with affective disorders on average have a higher body mass index (BMI) than the general population [63]. Nearly one in five patients with bipolar disorder have metabolic syndrome and from 16% up to 36% have components of it [65].…”
Section: Affective Disordersmentioning
confidence: 99%
“…Meta-analytic studies are an indispensable tool for bringing clarity to a disparate body of literature; however, to date there has been only one meta-analysis conducted to examine the relationship between depression and serum LDL. In 2008, Shin et al conducted a meta-analysis of 11 observational studies (Lindberg, Larsson et al 1994, Olusi and Fido 1996, Rutledge, Reis et al 2001, Sevincok, Buyukozturk et al 2001, Aijanseppa, Kivinen et al 2002, Pozzi, Troisi et al 2003, Ergun, Uguz et al 2004, Huang and Chen 2004, Karlovic, Buljan et al 2004, Elovainio, Keltikangas-Jarvinen et al 2006, Roy and Roy 2006) to evaluate the association between depression and serum LDL and determined there to be a non-significant inverse association (d = −0.17, 95% CI = −0.44, 0.10) (Shin, Suls et al 2008). The meta-analysis conducted by Shin et al included studies published through 2006; subsequent to 2006, there have been 23 additional studies conducted to examine the association between depression and serum LDL.…”
Section: Introductionmentioning
confidence: 99%
“…[8] However, interestingly, reflection of the vital role of cholesterol in maintaining this optimum membrane protein function has not been found to be consistent with its serum level as reported by several studies, and some of them, including some recent ones, have put doubts on the link between serum cholesterol level and psychiatric disorders as they could not find out any significant correlation between the two. [910] Moreover, studies have reported that there is no correlation between the serum and red blood cell (RBC) membrane cholesterol levels, and some have found even an increase in serum cholesterol levels with decreased RBC membrane cholesterol that is accompanied with an inhibition of the sodium pump activity. [11] These incongruent observations necessitated exploration of the role of membrane cholesterol itself in maintenance of the NKA activity.…”
Section: Introductionmentioning
confidence: 99%